Serum human epididymis protein 4 vs carbohydrate antigen 125 for ovarian cancer diagnosis: a systematic review. Issue 4 (20th February 2013) - Ferraro, Simona; Braga, Federica; Lanzoni, Monica; Boracchi, Patrizia; Biganzoli, Elia Mario; Panteghini, Mauro
Abstract : Background: Human epididymis protein 4 (HE4) measurements in serum have been proposed for improving the specificity of laboratory identification of ovarian cancer (OC). Objective: To critically revise the available literature on the comparison between the diagnostic accuracy of HE4 and carbohydrate antigen 125 (CA-125) to confirm the additional clinical value of HE4. Methods: A literature search was undertaken on electronic databases and references from retrieved articles; articles were analysed according to predefined criteria. Meta-analyses for HE4 and CA-125 biomarkers with OR, diagnostic sensitivity, specificity, positive (LR+) and negative (LR–) likelihood ratios as effect sizes were performed. Results: 16 articles were originally included in meta-analyses, but two for HE4 and one for CA-125 were eliminated as outliers. Furthermore, for HE4 a publication bias was detected. ORs for both HE4 (37.2, 95% CI 19.0 to 72.7, adjusted for publication bias) and CA-125 (15.4, 95% CI 10.4 to 22.8) were significant, although in a heterogeneous set of studies (p<0.0001). By combining sensitivity and specificity, the overall LR+ and LR– were 13.0 (95% CI 8.2 to 20.7) and 0.23 (95% CI 0.19 to 0.28) for HE4 and 4.2 (95% CI 3.1 to 5.6) and 0.27 (95% CI 0.23 to 0.31) for CA-125, respectively. Conclusions: HE4 measurement seems to be superior to CA-125 in terms of diagnostic performance for identification of OC in women with suspected gynaecological disease. Due to the high prevalence of OC in post-menopausal women and the need for data focused on early tumour stages, more studies tailored on these specific subsets are needed.